Effect of acrylamide on the degradation of palm-based used cooking oil by single and co-culture isolates of Alcaligenes sp. AQ5-02 and Serratia sp. AQ5-03 - Ahmed, Mariyam Shabeea; Ahmad, Siti Aqlima; Shukor, Mohd Yunus; Yusof, Mohd Termizi (Malaysian Society for Biochemistry and Molecular Biology, 2023)
Acrylamide is found in the environment, food, and waste products such as palm-based used cooking oil (UCO). The presence of acrylamide is a threat due to its neurotoxic, genotoxic, teratogenic, and carcinogenic characteristics. These negative impacts have sparked an interest in microbe-mediated bioremediation of acrylamide. The aim of this study is to investigate the effect of various concentrations of acrylamide on the degradation of UCO as a sole carbon source by single and co-culture isolates of Alcaligenes sp. AQ5-02 and Serratia sp. AQ5-03. Using gravimetric analysis, different acrylamide concentrations ranging from 10-200 mg/L were shown to significantly reduce palm oil UCO degradation and bacterial growth in single and co-culture formulations. In the co-culture, there were significant differences between all acrylamide concentrations in terms of UCO degradation. The single and co-culture isolates were able to withstand 10 mg/L of acrylamide while degrading more than 50 of UCO. However, beyond 10 mg/L, there was a significant reduction in the degradation of UCO in both single and co-culture methods. Two-way ANOVA reveals a significant difference in the degradation and bacterial growth between the single and co-culture isolates of Alcaligenes sp. AQ5-02 and Serratia sp. AQ5-03 with varying acrylamide concentrations (p < 0.0001). In conclusion, the co-culture has greater degradation and better tolerance at all concentrations of acrylamide compared to single isolate cultures of Alcaligenes sp. AQ5-02 and Serratia sp. AQ5-03. The study provides insightful knowledge on the presence of xenobiotics in the bioremediation of hydrocarbons by single and co-culture.